Comparing the patients' subjective experiences of acute side effects during radiotherapy for head and neck cancer with four different patient-reported outcomes questionnaires. (4th May 2019) - Holländer-Mieritz, Cecilie; Johansen, Jørgen; Johansen, Christoffer; Vogelius, Ivan R.; Kristensen, Claus A.; Pappot, Helle
Abstract: Background: The systematic use of a Patient-Reported Outcome (PRO) as symptom monitoring during cancer treatment and follow-up has the potential to increase symptom awareness, secure timely management of side effects, improve health-related quality of life and improve data quality. This study was conducted to identify the patients' experience during chemoradiotherapy for squamous cell carcinoma of the head and neck (HNSCC) and to investigate how these symptoms correspond with different PRO questionnaires. Material and methods: Semi-structured interviews on acute side effects were performed until saturation with HNSCC patients treated with high-dose radiotherapy (RT) ± concomitant chemotherapy. The symptoms were thematically grouped in organ classes in accordance with Medical Dictionary for Regulatory Activities (MedDRA). PRO questionnaires validated for patients with HNSCC during RT were identified in the literature and were compared to the patients' symptoms. Results: Thirteen patients were interviewed. The most frequently mentioned symptoms were oral pain, decreased appetite, dysphagia, dry mouth, fatigue and hoarseness, in order of frequency. A comparison between the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire for Head and Neck Cancer (EORTC QLQ-H&N35), the Functional Assessment of Cancer Therapy General and Head and Neck (FACT-H&N), the M.D. Anderson Symptom Inventory Head and Neck questionnaire (MDASI-HN), selected items from the Patient-Reported Outcomes Version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE) and the symptoms described by the patients showed that the PROs do not cover the same symptoms, and no specific questionnaire covers all patient's experiences. Conclusion: We find, that questionnaires applied in the field of PRO among patients with HNSCC undergoing RT may not fully comprise the experiences of patients and we recommend, that experiences of patients must be included in the design of trials involving PRO, in order to decrease the likelihood of missing out reports of acute side effects.